Efficient 3D temperature propagation for laser glass interaction - Alias, Norma; Shahril, Rosdiana; Islam, Md. Rajibul; Satam, Noriza; Darwis, Roziha (2008)
A new algorithm in the class of the AGE method is for developed to solve the heat equation in 3 space dimensions laser glass model problem. AGE method is one of the iterative, convergent, stable and second order accurate with respect to space and time. All the parallel strategies were developed on a CPUs. The distributed parallel computer system was run on the homogeneous cluster of 20 Intel Pentium IV PCs, each with a storage of 20GB and speed of 1.6 MHz. where data decomposition is run asynchronously and concurrently at every time level. The performance evaluations of the algorithm are increasing in terms of speed-up, efficiency and effectiveness.